Pola Komunikasi antara Masyarakat etnik Toraja dan etnik Pendatang di Kota Rantepao Toraja Utara (Studi Komunikasi Antarbudaya) - Kiki Fatmala; Muliadi Muliadi; Zelfia Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2020)
The purpose of this study was to determine the communication pattern between the Toraja ethnic community and ethnic immigrants in North Rantepao Toraja City and to find out how to adjust communication and behavior between the Toraja ethnic community and the immigrant ethnic community in the North Rantepao Toraja City. This study used descriptive qualitative research methods. This study seeks to reveal data or information related to communication patterns between the Toraja Ethnic Community and Ethnic Immigrants in North Rantepao Toraja City. The informants selected in this study were determined based on certain criteria. This research was conducted by collecting data through observation, interviews, and documentation. This research was conducted for one month and is located in the city of Rantepao, North Toraja. The results showed that the immigrant ethnic community living in Rantepao City used Indonesian and Toraja as their daily language. The communication process that occurs between the Toraja ethnic community and ethnic immigrants is a process of adaptation to the environment and the process of repeating messages. Then from this process was born the communication pattern used by the Toraja ethnic community and ethnic immigrants in communicating, namely the two-way communication pattern and the interactive, transactional and dynamic multi-way communication pattern. Where between the two ethnic groups exchange functions that run naturally without taking into account the very striking language differences between the two different ethnicities, so that harmony between them is maintained and there are no misunderstandings. Because the immigrant ethnic community has been able to adjust their behavior and understand the language used by the Toraja ethnic community because they often interact and greet each other when they meet, they can understand and respect each other.